Christian Faith and Violence 2 - Keulen, Dirk van,; Brinkman, Martien, (Studies in Reformed Theology;, 2005)
Volumes 10 and 11 of Studies in Reformed Theology consist of the texts written for the fifth international conference of the International Reformed Theological Institute (IRTI) , which was dedicated to the theme, 'Christian Faith and Violence'. Specific theological questions were at the core of the discussions, e.g. what does violence imply for the doctrine of God? How to deal with biblical stories and commands that often contain an overwhelmingly violent character? What about applying christian ethics in situations of violence that we are exposed to? What is our calling in situations of oppression and a longing for liberation and justice?.